Faktor-faktor Penyebab Pendeta Perempuan Menjadi Korban KDRT di Kota Kupang Provinsi Nusa Tenggara Timur: Dari Perpespektif Gereja Masehi Injili di Timor - Mesakh A.P. Dethan; Isakh A. Hendrik; Magdalena Ngongo; Julian Widodo (Missio Ecclesiae, 2021)
This study aims to determine the extent of the factors that cause female pastors to become victims of domestic violence and to what extent the Evangelical Christian Church in Timor has handled domestic violence experienced by female pastor, which can be used as a study and learning material in preventing and overcoming. Violence against female pastors. The method used in this research is qualitative research methods. The qualitative research approach was chosen because it emphasizes on phenomena/facts, the meaning of reasoning, certain situations (in certain contexts), or more research on matters related to the daily lives of women who are victims of domestic violence. From the results of the study, it was found that the factors causing domestic violence were due to jealousy from the husbands, as well as economic pressures. Causative factors also occur due to husbands who on average are drunkards and like to gamble, husbands who have less education than their wives, husbands who are hypersexual, husbands who experience psychological disorders, and also because wives are too busy with their service duties so that their husbands are feeling abandoned. The GMIT effort in this case carried out by UPP Pastoral as an extension of the MSH GMIT is considered not yet carrying out its mentoring function effectively to pastors who are victims of domestic violence. The victims felt that the services provided were still limited to providing advice without conducting any deepening of the problems experienced by the victims. For this reason, the functions of pastoral bodies in all spheres need to be optimized in a planned manner as a form of psychosocial support to prevent and break the chain of domestic violence. The research results also show that the church does not yet have a procedure or SOP that allows the recovery process for the victims to be carried out in a planned and systematic manner. The victims are also increasingly stressed because in addition to losing their income due to being withdrawn from their ministry as pastors, they also get negative stigma from their fellow pastors and congregations.